Quantitative 3-D Model of Carbonate Reef and Shoal Facies Based on UAV Oblique Photogrammetry Data: A Case Study of the Jiantanba Outcrop in West Hubei, China - Yin, Senlin; Zhao, Lei; Lin, Yu; Zhu, Baiyu; Zhao, Junwei; Cheng, Leli (Frontiers in Earth Science, 2022)
Aiming at the problem of insufficient data acquisition for steep carbonate outcrops, we used unmanned aerial vehicle oblique photogrammetry to quantitatively evaluate Jiantianba outcrops from a global perspective. This method can quickly and flexibly acquire, process and interpret outcrop data, establish the three-dimensional digital outcrop model and quantitative reservoir geological knowledge database. Through the fine analysis and comparative study of multiple outcrop sections, we use lithofacies combination, hierarchical interface, sequential indicator stochastic simulation and multiple-point geostatistical simulation methods to establish a three-dimensional multi-point statistical model of the outcrop area. The results show that the model of the Jiantianba carbonate outcrop has three-dimensional coordinates that correspond to oblique photograph image data, allowing for both the accurate location of any point and the measurement of the rock body, and thus providing a base for studying the stratigraphic architecture of the outcrop. Through fine-scale geological and statistical analyses of the geological parameters of three geologic sections, we established a database and model of a typical outcrop, including the types, continuity and scale of lithology, as well as different lithological combinations and the geological evolution of the region. And we established a geological model and quantitative geological database via sequential indicator simulation, using virtual well location, lithological combination, stratigraphic correlation, three-dimensional stratigraphic and lithological models of a typical outcrop. Subsequently, we analyzed the training images of different microfacies based on these models combined with the outcrop geometry. Finally, we established a three-dimensional geological model of reef–shoal facies that is more in line with our current understanding of the geology of the outcrop area by multi-point geostatistical simulations.